(untitled) (Baghdad Science Journal, 2025)
The present study was carried to evaluate antibacterial activity of Acetone, Alcholic (cold and hot) and Aqueaus(water) extracts of Citrus aurantifoliaseeds,against growth of some bacteria isolated from burns infections(Pseudomonas aeruginosa,Escherichia coli, Klebsiellapneumonia,Staphylococcusaureus)fromKindy HospitalIn Baghdad from March to June 2012.Antibiotic Sensitivity was done for all isolated bacteria used in this study.Results showed variation in antibacterial activity of different extracts against all tested bacteria by well diffusion technique in agar and measuring the diameter of inhibition zone, at concentration 250Mg-ml. Acetone extract had the greatest inhibitory effect followed by hot alcoholci extract, and then cold alcoholic extract,while the aqueous extract slightly inhibited bacteria. Minimum inhibitory concentration(MIC)were determined for all extracts against studying bacteria and found(12.5-50)mg-ml for acetone and alcoholic extracts, MIC for aqueous extract was 50mg-ml forPseudomonasaeruginosa and Escherichia coli,while was no effect onKlebsiellapneumonia and Staphylococcusaureus. Minimum Bacterial Concentration(MBC)were determined and was found25-50mg-ml for acetone extract,hot water was25mg-ml, cold alcoholic extract was 50mg-ml forPseudomonasaeruginosa,Escherichia coli andKlebsiella pneumonia but showed no effect on Staphylococcus aureus, aqueous extract showed negative effect on alltested bacteria. The antimicrobial activity of hot alcoholic extract of seeds was investigated practically (in vivo) by treating burns mices infected with tested bacteria(Pseudomonas aeruginosa,Escherichia coli and Klebsiellapneumonia),the results revealed good recovery at short time comparing with antibiotic(Flamazine) used at the same time.